Strategies for Increasing School Readiness in Accepting Students with Special Needs through Inclusive Education - Malintang, Jimmy; Najmi, Akmalun; Fahmi, Fahmi; Cindrya, Elsa; Iffah, Izzatul (Universitas Pahlawan Tuanku Tambusai, 2025)
Inclusive education has become a global priority, aiming to provide equitable learning opportunities for all students, including those with disabilities. However, despite the increasing emphasis on inclusion, many schools face challenges in fully preparing to support students with diverse needs. This study identifies strategies to improve school readiness to welcome students with disabilities through inclusive education. The research used a qualitative case study approach; data were collected from semi-structured interviews, focus group discussions, and document analysis conducted in three inclusive schools. The study findings indicate that leadership commitment, teacher training, collaborative support systems, and family involvement strongly influence school readiness. Schools with visionary leadership, ongoing professional development for teachers, and strong community engagement demonstrated higher readiness levels for inclusion. However, challenges such as inadequate resources and persistent community stigma against disability were identified as barriers. The study concludes that school readiness for inclusion is an ongoing process that requires a whole-school approach that integrates leadership, instructional practices, and community engagement